2011
DOI: 10.1111/j.1464-410x.2011.10757.x
|View full text |Cite
|
Sign up to set email alerts
|

Predicting erectile function outcome in men after radical prostatectomy for prostate cancer

Abstract: What's known on the subject? and What does the study add? Over the last decade, the surgical treatment of prostate cancer has evolved towards minimal access surgery, particularly via a robot‐assisted technique. However, there is still debate regarding the true benefit for patients with respect to a functional outcome such as erectile function. The present prediction model provides a reliable estimation of the likelihood of regaining erectile function after prostatectomy. OBJECTIVE To identify the reported rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
38
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 16 publications
6
38
0
Order By: Relevance
“…For example, Ficarra et al reported that at 12 months post-RARP, potency recovered between 54 and 90% and at 24 months between 63 and 94% [4]. According to Kilminster et al potency at 48 months varied between 60-100% [11]. Our results show a 74.8% EF recovery in the first year after RARP, which is close to the above results.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…For example, Ficarra et al reported that at 12 months post-RARP, potency recovered between 54 and 90% and at 24 months between 63 and 94% [4]. According to Kilminster et al potency at 48 months varied between 60-100% [11]. Our results show a 74.8% EF recovery in the first year after RARP, which is close to the above results.…”
Section: Discussionsupporting
confidence: 81%
“…There are several studies that perform systematic reviews and meta-analyzes of the EF after RARP [4,11]. For example, Ficarra et al reported that at 12 months post-RARP, potency recovered between 54 and 90% and at 24 months between 63 and 94% [4].…”
Section: Discussionmentioning
confidence: 99%
“…(8, 1114, 1721) One study was a metaanalysis of multiple studies of erectile dysfunction, which was limited by poor study design (failure to account for between-study variability). (10)…”
Section: Resultsmentioning
confidence: 99%
“…(10, 12, 13, 17, 18, 20) An example is the study by Romond et al, in which the authors suggest that their clinical risk score can be used to balance the benefits and harms of adding trastuzumab to the standard chemotherapy regimen in breast cancer. (17) One application to survivorship is the use of the prediction model for patient counseling and setting expectations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation